Generation of an Artificial Intestine for the Management of Short Bowel Syndrome - Ladd, Mitchell R. (Curr Opin Organ Transplant, 2016)
PURPOSE OF REVIEW: To discuss the current state of the art in artificial intestine generation in the treatment of short bowel syndrome. RECENT FINDINGS: Short bowel syndrome defines the condition in which patients lack sufficient intestinal length to allow for adequate absorption of nutrition and fluids, and thus need parenteral support. Advances towards the development of an artificial intestine have improved dramatically since the first attempts in the 1980s, and the last decade has seen significant advances in understanding the intestinal stem cell niche, the growth of complex primary intestinal stem cells in culture, and fabrication of the biomaterials that can support the growth and differentiation of these stem cells. There has also been recent progress in understanding the role of the microbiota and the immune cells on the growth of intestinal cultures on scaffolds in animal models. Despite recent progress, there is much work to be done before the development of a functional artificial intestine for short bowel syndrome is successfully achieved. SUMMARY: Continued concerted efforts by cell biologists, bioengineers and clinician-scientists will be required for the development of an artificial intestine as a clinical treatment modality for short bowel syndrome.